Mitochondrial Complex II: At the Crossroads - Bezawork-Geleta, Ayenachew; Rohlena, Jakub; Dong, Lanfeng; Pacak, Karel; Neuzil, Jiri (Trends in biochemical sciences, 2017)
Mitochondrial complex II (CII), also called succinate dehydrogenase (SDH), is a central purveyor of the reprogramming of metabolic and respiratory adaptation in response to various intrinsic and extrinsic stimuli and abnormalities. In this review we discuss recent findings regarding SDH biogenesis, which requires four known assembly factors, and modulation of its enzymatic activity by acetylation, succinylation, phosphorylation, and proteolysis. We further focus on the emerging role of both genetic and epigenetic aberrations leading to SDH dysfunction associated with various clinical manifestations. This review also covers the recent discovery of the role of SDH in inflammation-linked pathologies. Conceivably, SDH is a potential target for several hard-to-treat conditions, including cancer, that remains to be fully exploited.
Keywords: Mitochondria; Animals; Inflammation; Humans; Succinate Dehydrogenase; mitochondrie; lidé; zvířata; zánět; sukcinátdehydrogenasa